Fertilizer Treatment on Postharvest Appearance of White Radish Tubers in Drip Irrigation System - Desianti, Sabrina; Inti Mulyo, Arti; Risnawati, Risnawati; Julio Aria, Nugraha (Jurnal Biologi Tropis, 2025)
Appearance tends to influence consumer judgement including appearance, size, dimensions, yield and hardness of agricultural products. This study aims to observe the appearance, length, diameter, yield and texture of postharvest white radish tubers due to fertilizer treatment in drip irrigation system. The study used a 2-factor Randomised Complete Block Design (RCBD). The first factor was NPK festiliser with concentrations of 0 kg/ha (N0), 400 kg/ha (N1), and 700 kg/ha (N2). The second factor was cow manure fertilizer at 0 tonnes/ha (P0), 15 tonnes/ha (P1) and 30 tonnes/ha (P3). Data were analyzed using ANOVA test, and DMRT 0,5% follow-up test. Parameters observed besides appearance were length, diameter, yield and texture of white radish tubers. The results showed that the appearance of white radish tubers tended to be influenced by the growing environment. NPK fertilizer had a significant effect on the length and very significant effect on the diameter of white radish tubers. Cow manure fertilizer had a significant effect on the diameter of white radish tubers. The interaction of the two factors had no significant effect on all parameters observed.